A brief history of entrepreneurship : the pioneers, profiteers, and racketeers who shaped our world - Carlen, Joe (Columbia Business School series., 2016)
"Through engaging vignettes, A Brief History of Entrepreneurship charts how the pursuit of profit by private individuals has been a prime mover in revolutionizing civilization. Entrepreneurs often butt up against processes, technologies, social conventions, and even laws. So, they circumvent, innovate, and violate to obtain what they want. This creative destruction has brought about overland and overseas trade, colonization, and a host of revolutionary technologies -- from caffeinated beverages to the personal computer -- that have transformed society. Consulting rich archival sources, including some that have never before been translated, Carlen maps the course of human history through nine episodes in which entrepreneurship reshaped our world. In an engaging style highlighting the most colorful characters of each era, he discusses Mesopotamian merchants' creation of the urban market economy; Phoenician merchant-sailors intercontinental trade that came to connect Africa, Asia, and Europe; Chinese tea traders' invention of paper money; the colonization of the Americas; and the current 'flattening' of the world's economic playing field. All of these are products of the entrepreneur's profit-driven quest. Yet the pursuit of profit hasn't always been positive. From slavery to organized crime, Carlen explores how entrepreneurship can sometimes work at the expense of others. Lastly, he discusses the new entrepreneurs who, through the nascent space tourism industry, are leading humanity to a multiplanetary future. By exploring all sides of this colorful and controversial legacy, Carlen brings much-needed detail to the role of entrepreneurship in shaping the course of history"--Provided by publisher